DAMPAK CORPORATE SOCIAL RESPONSIBILITY,GOOD CORPORATE GOVERNANCE TERHADAP REPUTASI PERUSAHAAN PERTAMBANGAN DI INDONESIA - Irmayanti Sudirman; Dwi Ningrum (AkMen JURNAL ILMIAH, 2022)
The purpose of this research is that CSR and GCG are activities carried out to provide value to the community and the surrounding environment. So that it can have an impact on the company's positive image which affects the company's reputation and the continuity of the company in the future, especially mining companies in Indonesia. This research method is descriptive quantitative using secondary data, data from the 2018-2020 financial reports.This research was conducted at mining companies in Indonesia. As for the sampling of 46 mining companies using saturated sampling technique, namely sampling from the entire population. The test results show that the Partial Test CSR, has a significance value of 0.000<0.05 and a calculated t value of 5.620> from t table 1,681. This shows that CSR has a significant and significant effect on company reputation.Furthermore, for GCG a significance value of 0.088>0.05 and a t count value of 1.746> from t table 1,681 indicates that GCG is not significant but has an effect on the company's reputation. Meanwhile, the results of the Simultaneous Test CSR and GCG have a significance value of 0.000<0.05 and the calculated f value is 16.405 > from t table 1.681. This shows that CSR and GCG simultaneously have a significant effect on the company's reputation.